Multisectoral household domestic and healthcare waste management in DIY - Purwati, Alvi; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2021)
PIYUNGAN LANDFILL, DIY The Piyungan Landfill with an area of ​​12.5 hectares is managed by DLHK DIY and accommodates waste from Yogyakarta City, Sleman, and Bantul. Since 2014, the capacity of the Piyungan Landfill is not sufficient to manage the rapidly generated waste. In early 2020, Piyungan TPA receives 560-580 tons of waste every day. At the end of 2020, the capacity of the Piyungan TPA will be increased to 438,000 tons which are expected to last for the next two years. WASTE REDUCTION FROM GENERATING SOURCES Garbage arises from various sources, so cooperation from various parties is needed. DLHK DIY needs to make a “garbage emergency” statement to raise public awareness. Especially for the Waste Sector, DLHK DIY, it is necessary to implement a policy of “only transporting sorted waste” by using a truck to separate each type of waste. The community must sort waste into four types, namely organic, inorganic recyclable, inorganic non-recyclable, and waste from the care of sick people in the household. The Health Office through the Sanitarian Health Center needs to mobilize the community to sort and utilize the existing land to make compost from organic waste. Sanitarians also need to socialize with the community to pack waste from patient care at home in separate containers. Disperindag DIY needs to urge shopping locations not to provide shopping plastic bags for consumers. Disperindag also needs to urge producers to use packaging with similar materials in one product to make it easier to sort waste. Disperindag can also require the recycling industry to use recyclable inorganic waste. PROCESSING OLD WASTE The pile of garbage in the Piyungan TPA needs to be reduced quickly using a large capacity incinerator. DLHK DIY needs to provide funds for the procurement of incinerators or can also open sponsorships from companies in DIY. The Piyungan landfill manager also needs to recruit human resources capable of operating the incinerator. PROCESSING NEW WASTE The Piyungan landfill manager can divide the waste processing area into four, according to the sorting criteria carried out by the community. Organic waste that is not reduced upstream can be processed into large-scale compost that has economic value. Recyclable inorganic waste must be utilized by the recycling industry. Non-recyclable inorganic waste and waste from household patient care are burned with incinerators to destroy pathogens. With complete management, domestic waste problems can be controlled. _______________________________________________________________________________________________________________________________ TPA PIYUNGAN DIY TPA Piyungan seluas 12,5 hektar dikelola oleh DLHK DIY dan menampung sampah dari Kota Yogyakarta, Sleman, dan Bantul. Sejak 2014, kapasitas TPA Piyungan tidak memadai untuk mengelola sampah yang timbul secara pesat. Awal 2020, setiap hari TPA Piyungan mendapat 560-580 ton sampah. Akhir 2020, kapasitas TPA Piyungan ditambah menjadi 438.000 ton yang diharapkan dapat bertahan hingga dua tahun mendatang. REDUKSI SAMPAH DARI SUMBER TIMBULAN Sampah timbul dari berbagai sumber, maka diperlukan kerja sama dari berbagai pihak. DLHK DIY perlu membuat pernyataan “darurat sampah” untuk memunculkan kepedulian masyarakat. Khusus Bidang Persampahan DLHK DIY, perlu mengimplementasikan kebijakan “hanya mengangkut sampah yang sudah dipilah” dengan proses pengangkutan menggunakan truk bersekat untuk memisahkan setiap jenis sampah. Masyarakat harus memilah sampah menjadi empat macam yaitu organik, anorganik recyclable, anorganik non-recyclable, dan sampah dari perawatan orang sakit di rumah tangga. Dinkes melalui Sanitarian puskesmas perlu menggerakkan masyarakat untuk melakukan pemilahan dan memanfaatkan lahan yang ada untuk membuat kompos dari sampah organik. Sanitarian juga perlu menyosialisasikan kepada masyarakat untuk mengemas sampah dari perawatan pasien di rumah dengan wadah tersendiri. Disperindag DIY perlu mengimbau lokasi perbelanjaan agar tidak menyediakan kantong plastik belanja bagi konsumen. Disperindag juga perlu mengimbau produsen agar menggunakan kemasan dengan bahan sejenis pada satu produk agar memudahkan dalam hal pemilahan sampah. Disperindag juga dapat mengharuskan industri daur ulang untuk menggunakan sampah anorganik recyclable. PENGOLAHAN SAMPAH LAMA Tumpukan sampah di TPA Piyungan perlu direduksi dengan cepat menggunakan insinerator berkapasitas besar. DLHK DIY perlu menyediakan dana untuk pengadaan insinerator atau dapat juga membuka sponsorship dari perusahaan-perusahaan yang ada di DIY. Pengelola TPA Piyungan juga perlu merekrut SDM yang mampu mengoperasikan insinerator. PENGOLAHAN SAMPAH BARU Pengelola TPA Piyungan dapat membagi area pengolahan sampah menjadi empat, sesuai dengan kriteria pemilahan yang dilakukan oleh masyarakat. Sampah organik yang tidak tereduksi di hulu, dapat diproses menjadi kompos berskala besar yang memiliki nilai ekonomi. Sampah anorganik recyclable harus dimanfaatkan oleh industri daur ulang. Sampah anorganik non-recyclable dan sampah dari perawatan pasien rumah tangga dibakar dengan insinerator untuk memusnahkan patogen. Dengan pengelolaan yang paripurna, permasalahan sampah domestik dapat dikendalikan.